Home-cooked meals : remembering the taste of home. - Liew, Sharlen. (2013)
This is a study of the social memories relating to family food practices. Through qualitative interviews conducted with three sets of mother/grandmother and child, memories were gathered, and analysis of those memories was framed in notions of generational differences, and kinship relations. The conclusion was that social memories relating to family food practices served to contribute to the individual’s sense of self in relation to their family, and also in the construction of a family identity that is situated in a historical context, within a cultural group, and in relation to other families.